Peri-implantitis: current concepts about its etiology, clinical and imaging characteristics. A review - Martínez Gómez, Juan Carlos (2022)
Peri-implantitis (PI) is the inflammatory reaction of the peri-implant mucosa, accompanied by the progressive loss of supporting bone around the implant, which can compromise its stability, function and aesthetics. It is diagnosed by radiographic measurement of the alveolar bone level, with or without clinical symptoms of inflammation and a probing depth greater than 4 mm. The objective of this work was to review the scientific evidence on the prevalence, etiology, predisposing factors, clinical behavior and imaging characteristics of PI. An electronic search was carried out in Google Scholar, PubMed and Scielo, considering the period between 2010-2022, and a total of 40 articles were selected. It is concluded that the main etiological agent of PI is the biofilm, however, its appearance and severity may be associated with the presence of predisposing factors such as Diabetes Mellitus, smoking, pre-existing periodontal disease and absence of keratinized mucosa, among others. Clinically, PI is related to bleeding on probing, gingival recession, and suppuration. Imaging evaluation of the peri-implant defect is routinely performed with periapical radiographs; Recent use of cone-beam computed tomography has allowed three-dimensional assessment of the defect, although considerations of radiation dose to the patient and image artifacts have been made that may limit its extensive use.